THE LEGALITY OF THE OMNIBUS LAW FROM FULLER'S PERSPECTIVE - VERIDO DWIKI HERDHIANTO; SUNNY UMMUL FIRDAUS; ANDINA ELOK PURI MAHARANI (CV KULTURA DIGITAL MEDIA, 2022)
Omnibus can create legal certainty by directly regulating a bunch of facts that are intertwined in the legal system. This method is considered to be more effective than creating individual laws and regulations, which can lead to duplications and inconsistencies between regulations. Contrary to this ideal concept, the Indonesian Government's Comprehensive Law or Preparation Law must be conditionally overturned by the Constitutional Court by Constitutional Court Decision No. 91 / PUUXVIII / 2020. As the legislative body responsible for enacting the law, DPR has two years to fix the formal flaws in Undang Undang Cipta Kerja. This study uses the nature of the doctrine study, the conceptual approach, and the legal approach to describe the management aspects of Undang Undang Cipta Kerja as an omnibus method using Lon L. Fuller. This analysis provides an overview of the strengths and weaknesses of Undang Undang Cipta Kerja in terms of superior legal quality. Recognizing the weaknesses of publications that exist in the process of creating and implementing Undang Undang Cipta Kerja may be recommended to the government if it meets the formal improvement deadline required by the Constitutional Court to maintain omnibus law. I can do it. It will bring positive benefits to Indonesia's investment environment. Keywords: omnibus law, principle of legality, UU Cipta Kerja